Effects of Apricot and Apricot Kernels on Human Health and Nutrition: A Review of Recent Human Research - Jaafar, Hawar Jawdat (Technium BioChemMed, 2021)
Plants are one of the most important sources of medicine for humans to face diseases and disorders. Despite some advances in the field of allopathic system of medicine, adverse reactions have not been prevented from being an integral part of modern medicine. Plants are one of the important sources of drug discovery in both modern and traditional medicine systems worldwide. Recent developments in food and nutrition, consumer preferences shifted to foods rich in nutraceuticals. Furthermore 70% of marketed drugs are either natural or semisynthetic materials which derived from plants. Most literature on complementary alternative medicine worldwide either reports the nature of phytocomponents in medicinal plants or shows a mechanistic basis for their pharmacological activities. The medicinal and therapeutic effect of apricot has not been studied so far. In this review, an attempt has been made highlight the importance of apricot and its kernel in human health and nutrition by summarizing the literature reports published to date. Apricot exhibited diversified effects on degenerative diseases such as cancer, cardiovascular and hemostasis, at the same time has many pharmacological effects such as anti-parasitic, anti-aging, anti-atherosclerosis, renoprotective, hepatoprotective and antioxidant have been reported.